Спят усталые игрушки: стихи / З. А. Петрова ; художник Н. Салиенко - Петрова З. А. (Малыш, читай!, 2023)
Книжка-игрушка с вырубкой Экземпляры: ф.20 (2024) / Инвентарный номер: 60321 / Цена: 74.25. / Авт.знак: П30 / ББК: 84(2Рос=Рус)6